2012
DOI: 10.4040/jkan.2012.42.3.414
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Korean Nursing Delirium Scale

Abstract: Purpose: The aims of this study were to develop and test the validity of the Korean Nursing Delirium Scale (Nu-DESC) for older patients in hospital. Methods: The Korean Nu-DESC was developed based on the Nu-DESC (Gaudreau, 2005), and revised according to nursing records related to signs and symptoms of older patients with delirium (n= 361) and the results of a pilot study (n= 42) in one general hospital. To test the validity of the Korean Nu-DESC, 75 older patients whom nurses suspected of delirium from 731 ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…Two of the four excluded Nu‐DESC validation studies were studies using the criteria of DSM‐V as a reference standard test, but not performed or supervised by a psychiatrist or a neurologist (Abelha et al., 2013; Spedale et al., 2017). Another exclusion was due to insufficient data to derive a 2 × 2 table for evaluating Nu‐DESC test accuracy (Poikajarvi et al, 2017) and the other one used a modified, not an original, version of the Nu‐DESC (Kim, Kim, Kim, Yoo, & Park, 2012). Finally, we identified 11 articles that met our eligibility criteria, which were systematically reviewed and used in our meta‐analysis for DTA of the Nu‐DESC (Brich et al., 2018; Gaudreau et al., 2005; Hargrave et al., 2017; Heinrich et al., 2019; Leung et al., 2008; Lingehall et al., 2012; Luetz et al., 2010; Neufeld et al., 2013; Radtke et al., 2008, 2010; Saller et al., 2019).…”
Section: The Reviewmentioning
confidence: 99%
“…Two of the four excluded Nu‐DESC validation studies were studies using the criteria of DSM‐V as a reference standard test, but not performed or supervised by a psychiatrist or a neurologist (Abelha et al., 2013; Spedale et al., 2017). Another exclusion was due to insufficient data to derive a 2 × 2 table for evaluating Nu‐DESC test accuracy (Poikajarvi et al, 2017) and the other one used a modified, not an original, version of the Nu‐DESC (Kim, Kim, Kim, Yoo, & Park, 2012). Finally, we identified 11 articles that met our eligibility criteria, which were systematically reviewed and used in our meta‐analysis for DTA of the Nu‐DESC (Brich et al., 2018; Gaudreau et al., 2005; Hargrave et al., 2017; Heinrich et al., 2019; Leung et al., 2008; Lingehall et al., 2012; Luetz et al., 2010; Neufeld et al., 2013; Radtke et al., 2008, 2010; Saller et al., 2019).…”
Section: The Reviewmentioning
confidence: 99%
“…Three professional hospice nurses recorded the sPPI items upon their first home visit, and the additional assessment of delirium was made according to the Korean Nursing Delirium Screening Scale (Korean Nu-DESC). 20) The sPPI score was calculated using the PPS, oral intake, edema, dyspnea at rest, and CCS. The PPS was developed by modifying the Karnofsky Performance Scale and covers five aspects: ambulation, activity and evidence of disease, self-care, oral intake, and level of consciousness.…”
Section: Study Methodsmentioning
confidence: 99%
“…22) A score between 0 and 2 was assigned according to the degree of each item, but a study that introduced the Nu-DESC in Korea showed that there was no clear standard for determining the severity of each item. 20) Hence, it was modified to have a maximum score of 5 points. In this study, the presence of delirium was identified by a score of ≥2 points on the Korean Nu-DESC based on previous findings.…”
Section: Study Methodsmentioning
confidence: 99%
“…Its administration takes about two minutes and is accessible for clinical practice. It has been validated in different languages such as Danish (4), Turkish (5), Czech (6), and Korean (7), and used in different clinical practice scenarios: palliative care patients (8,9), cardiac surgery (10,11), liver transplantation (12), orthopedic surgery (13), urological surgery (14,15), scheduled post-operative patients (16)(17)(18)(19), post-anesthesia with medications such as ketamine (20), hospitalization (21), geriatrics hospitalization (22), oncologic hospitalization (23), and ICUs (24)(25)(26). The results of these studies report an average sensitivity of 96 % and specificity of 81 % using this scale.…”
Section: Introductionmentioning
confidence: 99%